IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TYPE NUMBERED HEAD TOGETHER (NHT) TO TRAIN SCIENCE PROCESS SKILL IN ACID BASE MATTER OF GRADE STUDENTS AT SMAN JOGOROTO JOMBANG - Rahmawati, Mulia Sri (Universitas Negeri Surabaya, 2019)
The purpose of this research is to describe Â the implementation of syntax of the numbered heads together (NHT) type of cooperative learning model and the students science process skills when applying the Numbered Heads Together (NHT) type of cooperative learning model to the acid base material. This research uses One-Group Pretest-Posttest Design. The results of the research are shown as follows: (1) The implementation of the syntax of the NHT types of cooperative learning model obtained a percentage at three meetings in the first phase of 62.5%, 75.0%, 87.0%; the second phase of 75.0%, 87.0%, and 100%; the third phase of 75.0%, 75.0%, and 100%; the fourth phase of 62.5%, 87.0%, and 100%; the fifth phase of 75.0%, 87%, 100%; the sixth phase 50%, 100%, and 100%. (2) Science process skills of students to formulate problems get n-gain values of 0.31 in the medium category, compile hypotheses to get n-gains value off 0.49 in the medium category, collecting data get n-gain values of 1,00 with a high category, analyzing the data get a n-gain value of 0.99 with a high category, and make conclusions to get a n-gain value of 0.92 with a high category.Keywords: numbered head together (NHT), science process skills, acid base.